2013
DOI: 10.1186/1472-6963-13-264
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary teams, and parents, negotiating common ground in shared-care of children with long-term conditions: A mixed methods study

Abstract: BackgroundLimited negotiation around care decisions is believed to undermine collaborative working between parents of children with long-term conditions and professionals, but there is little evidence of how they actually negotiate their respective roles. Using chronic kidney disease as an exemplar this paper reports on a multi-method study of social interaction between multidisciplinary teams and parents as they shared clinical care.MethodsPhases 1 and 2: a telephone survey mapping multidisciplinary teams’ pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…This means HCPs may not be aware of parents' needs and preferences, especially in the initial stages following diagnosis [34] when information provision and the formation of relationships is critical. HCPs may rely on their own 'tacit knowledge' to help determine how to pitch information [34], which can result in HCPs misjudging (often underestimating) parents' learning and information needs [28].…”
Section: Barriers To Parents' Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…This means HCPs may not be aware of parents' needs and preferences, especially in the initial stages following diagnosis [34] when information provision and the formation of relationships is critical. HCPs may rely on their own 'tacit knowledge' to help determine how to pitch information [34], which can result in HCPs misjudging (often underestimating) parents' learning and information needs [28].…”
Section: Barriers To Parents' Learningmentioning
confidence: 99%
“…Povlsen et al [27:41] suggested that with ethnic minority families it was useful for HCPs to ascertain parents' understanding of their child's condition and its 'impact on the family within the context of their cultural reality'. HCPs and parents discussing, and where possible sharing, concepts of LTCs, self-care and shared management was thought to facilitate parents' learning [34]. Some parents reported benefiting from meeting other parents of children with the same LTC [25] and from HCPs sharing anecdotes and anonymous examples of other families' learning [10,34].…”
Section: Facilitators To Parents' Learningmentioning
confidence: 99%
See 3 more Smart Citations